Association of cardiac autonomic modulation with different intensities of physical activity in a small Brazilian inner city: A gender analysis - Christofaro, Diego G.D. [UNESP]; Tebar, William R.; Vanderlei, Luiz Carlos M. [UNESP]; Fernandes, Rômulo A. [UNESP]; Mota, Jorge; Mielke, Gregore I.; Ritti-Dias, Raphael M. (Wiley, 2022)
Physical activity has been linked to higher cardiac autonomic modulation. However, it is not clear in the literature which type of intensity of physical activity (sedentary, light, moderate, or vigorous) could be related to better cardiac autonomic modulation and whether this relationship is similar in men and women. The aim of this study was to analyze the relationship between cardiac autonomic modulation and the different intensities of physical activity in men and women. The sample included 100 men and 131 women. Cardiac autonomic modulation was obtained by heart rate variability (SDNN, RMSSD, LF un, HF un, SD1, and SD2). Time spent in different intensities (sedentary, light, moderate, and vigorous intensity physical activity) was measured using a waist-worn accelerometer for seven days. Linear regression was used to verify the relationship between physical activity and cardiac autonomic modulation, considering the adjustment for age, ethnicity, and socioeconomic level. Among men, a significant relationship of moderate intensity was observed with SDNN (β = 2.442; p = 0.021) and SD2 (β = 2.936, p = 0.028), and of vigorous intensity with SDNN (β = 12.826, p = 0.028), RMSSD (β = 16.370, p = 0.018), and SD1 (β = 12.344, p = 0.025) indices. Among women, light-intensity physical activity was significantly related with LFnu (β =.655, p = 0.005) and HFnu (β = -.590, p = 0.010). Moderate and vigorous physical activity was associated with better cardiac autonomic modulation in men. Light physical activity was associated with lower sympathetic modulation in women.
Keywords: accelerometer; adults; exercise; Heart rate variability; sex